1999
DOI: 10.4049/jimmunol.163.9.5133
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Repertoire Diversity and Clonal Expansion in Multiple Sclerosis Brain Lesions

Abstract: Multiple sclerosis (MS) lesions in the CNS are characterized by disseminated demyelination with perivascular infiltrates of macrophages, T cells, and B cells. To investigate the origin and characteristics of the B cell population found in MS plaque tissue, we performed molecular studies in 10 MS patients and 4 non-MS control samples. Ig transcripts from the perivascular infiltrated brain lesions were analyzed by complementary-determining region 3 spectratyping to ascertain the B cell heavy chain gene rearrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The presence of B cells in recent MS plaques was first described in 1980 (Esiri, 1980), since then they were found to play a significant role in the pathology of the disease (reviewed in Wootla et al, 2011). As previously said, Baranzini et al were able to prove that a germinal center-like reaction takes place during the immune attack against CNS structures, with the production of antibodies within the plaques (Baranzini et al, 1999;Bradl and Lassmann, 2009;Kutzelnigg et al, 2005). Some of the roles attributed to these cells in MS pathology are: myelin-specific antigen presentation (acute demyelination and contribution to MS progression), abnormal cytokine production (decreased production of IL-10 may be responsible for the activation of proinflammatory T cells), and the production of immunoglobulins involved in demyelination or remyelination (reviewed in Wootla et al, 2011).…”
Section: Immune Cellsmentioning
confidence: 94%
“…The presence of B cells in recent MS plaques was first described in 1980 (Esiri, 1980), since then they were found to play a significant role in the pathology of the disease (reviewed in Wootla et al, 2011). As previously said, Baranzini et al were able to prove that a germinal center-like reaction takes place during the immune attack against CNS structures, with the production of antibodies within the plaques (Baranzini et al, 1999;Bradl and Lassmann, 2009;Kutzelnigg et al, 2005). Some of the roles attributed to these cells in MS pathology are: myelin-specific antigen presentation (acute demyelination and contribution to MS progression), abnormal cytokine production (decreased production of IL-10 may be responsible for the activation of proinflammatory T cells), and the production of immunoglobulins involved in demyelination or remyelination (reviewed in Wootla et al, 2011).…”
Section: Immune Cellsmentioning
confidence: 94%
“…Supernatants from cultured B cells from MS patients were toxic and induced more significant apoptosis in cultured neurons and oligodendrocytes than supernatants from cultured B cells from healthy controls 139,140 . The same antigen‐experienced B cell clones were found in meningeal immune cell infiltrates, the CSF and perivascular parenchymal lesions 141–143 . In addition, it has been demonstrated that B cell clones are bidirectionally exchanged between the CNS and the periphery and that affinity maturation occurs on both sides of the blood–brain barrier 144 .…”
Section: Immuno‐pathological Mechanismsmentioning
confidence: 99%
“…139,140 The same antigen-experienced B cell clones were found in meningeal immune cell infiltrates, the CSF and perivascular parenchymal lesions. [141][142][143] In addition, it has been demonstrated that B cell clones are bidirectionally exchanged between the CNS and the periphery and that affinity maturation occurs on both sides of the blood-brain barrier. 144 More recently, a study in mouse models suggested that meningeal B cells encompass multiple stages of development and may originate in calvaria and then infiltrate and maturate in the meninges via a network of channels uncoupled from the systemic circulation.…”
Section: Alterations In Normal Appearing White and Grey Mattermentioning
confidence: 99%
“…One of the earliest biochemical observations of MS was the presence of cerebrospinal fluid (CSF) oligoclonal IgG bands (4). Oligoclonal bands (OCBs) are accompanied by elevated numbers of clonally expanded B cells and plasmablasts in CSF, meninges, and brain tissue (5)(6)(7)(8)(9)(10). Deep sequencing of B cell repertoires established clonal relationships between CSF IgG OCBs and CSF B cell clones (11) and among CSF and meningeal and MS lesion B cell infiltrates (12).…”
Section: Introductionmentioning
confidence: 99%